Development of Student Worksheets on Environmental Pollution Based on Problem-Based Learning Oriented to Local Wisdom to Increase Students' Learning Motivation - Wawan Muliawan; M. Marzuki; Laeli Rizki Amalia (Universitas Sebelas Maret, 2024)
This research is based on the urgency of teaching materials or learning intermediaries. Considering that several factors make learning less than optimal, which has an impact on student motivation and learning outcomes. However, teacher and student statements emphasize that most of the learning is still emphasized on providing teacher-focused/centered theory. Hence, this research aims to develop Student Worksheets (LKPD) that focus on environmental pollution based on Problem-Based Learning (PBL) oriented to local wisdom, which is expected to increase student learning motivation. The research method used is research and development, which refers to the Borg & Gall procedure, which involves six stages: preliminary research, planning, initial product development, expert testing and initial field trials, revision of initial field trial results, and main field trials. The research design is to test a learning device product in the form of a Student Worksheet (LKPD) on environmental pollution based on local wisdom-oriented Problem-Based Learning (PBL) to identify things that need to be considered and completed in developing the Student Worksheet (LKPD). which is suitable for use. The data collection technique in this research is through giving validation sheets/questionnaires to material experts, design experts, and Biology subject teachers. Qualitative data analysis techniques and quantitative data analysis were used to process data based on validation results and trials on developing a Problem-Based Learning (PBL)-based Environmental Pollution Student Worksheet (LKPD) oriented to local wisdom. The assessment results from qualitative and quantitative data analysis obtained from material experts obtained an average of 3.68, design experts 3.33, first science teacher 3.35, second science teacher 3.27, and student responses 3.41, which included the criteria of Decent and Very Decent. Furthermore, product validity is based on the percentage score from material experts 92%, design experts 83.33%, first science teacher 83.75%, second science teacher 81.87%, and student responses 85.25%, which includes Very Good criteria. The implementation of the main field test showed an increase in student learning motivation in the experimental class by 0.52% and 0.42% in the control class. Therefore, broader research is needed to determine environmental pollution based on local wisdom